2022
DOI: 10.3390/antiox11122427
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Production of Hydroxycinnamoyl-Quinic Acids: From Natural Sources to Biotechnology

Abstract: Hydroxycinnamoyl-quinic acids (HCQAs) are polyphenol esters formed of hydroxycinnamic acids and (-)-quinic acid. They are naturally synthesized by plants and some micro-organisms. The ester of caffeic acid and quinic acid, the chlorogenic acid, is an intermediate of lignin biosynthesis. HCQAs are biologically active dietary compounds exhibiting several important therapeutic properties, including antioxidant, antimicrobial, anti-inflammatory, neuroprotective, and other activities. They can also be used in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 145 publications
0
8
0
Order By: Relevance
“…They have shown antioxidant, antimicrobial, antiviral, and anti-inflammatory activity, as well as risk reduction of developing type 2 diabetes and cardiovascular diseases [47]. Despite the antimicrobial activity, some microorganisms are resistant to chlorogenic acids because of their ability to degrade such compounds [47]. In this study, caffeoylquinic acid isomers a and b and coumaroylquinic acid isomers b and d decreased in fermentations with P. acidilactici CECT 5765T, P. pentosaceus CECT 923, Leu.…”
Section: Quantification Of Phenolic Compounds By Hplc-esi-tof-ms and ...mentioning
confidence: 62%
See 1 more Smart Citation
“…They have shown antioxidant, antimicrobial, antiviral, and anti-inflammatory activity, as well as risk reduction of developing type 2 diabetes and cardiovascular diseases [47]. Despite the antimicrobial activity, some microorganisms are resistant to chlorogenic acids because of their ability to degrade such compounds [47]. In this study, caffeoylquinic acid isomers a and b and coumaroylquinic acid isomers b and d decreased in fermentations with P. acidilactici CECT 5765T, P. pentosaceus CECT 923, Leu.…”
Section: Quantification Of Phenolic Compounds By Hplc-esi-tof-ms and ...mentioning
confidence: 62%
“…Their occurrence in plants has been associated with lignin biosynthesis, as an indirect defense agent, making tissues more resistant to pathogen attacks and inhibiting fungal toxins, and as a protective agent against oxidative damage caused by exposition to salinity and heat [45]. They have shown antioxidant, antimicrobial, antiviral, and anti-inflammatory activity, as well as risk reduction of developing type 2 diabetes and cardiovascular diseases [47]. Despite the antimicrobial activity, some microorganisms are resistant to chlorogenic acids because of their ability to degrade such compounds [47].…”
Section: Quantification Of Phenolic Compounds By Hplc-esi-tof-ms and ...mentioning
confidence: 99%
“…Several studies indicate that derivatives of QA, such as CA and GA, possess beneficial health effects, including antioxidant, antimicrobial, anti-inflammatory, and neuroprotective properties. Additionally, these compounds are absorbed and metabolized within the human gastrointestinal system [82,83]. Saravanan and Aradhya [84] reported that CC, ferulic, and PA help prevent cardiovascular, cancer, neurodegenerative diseases, oxidative stress, inflammation, DNA damage, and displayed anticancer, antidiabetic, and antihypertensive properties.…”
Section: Changes In Phenolic Acidsmentioning
confidence: 99%
“…Thus, numerous flavonoids have been identified in spruce and fir biomass (bark and needles), including the following: flavanols (epigallocatechin, dihydrokaempferol, cedeodarin, taxifolin, and derivatives), flavones (tricin, vitexin, vitexin-2-o-rhamnoside, myricetin-3-o-rhamnoside, kaempferol-3-rutinoside, kaempferol/luteolino-glucoside), isoflavones (afromosin, pratensein, glycitein, daidzein), flavanones (liquiritigenin, pinostrobin), chalcones (phloretin and phloretin-2-glucoside), and proanthocyanidins (proanthocyanidin, procyanidin B1/B2, procyanidin A2). Other bioactive compounds identified in the coniferous biomass included phenol phytochemicals, such as phenolic acids (quinic, shikimic, salicylic, vanillic, caffeic, synaptic, homovanilic) and derivatives (caffeoylquinic and 3-p-coumaroylquinic, caffeoylshikimic, 4-methoxycinnamic and toluic acids, and ferulic and vanillic acid glucosides), with antioxidant, antimicrobial, antiinflammatory, neuroprotective, anticarcinogenic, and antidiabetic properties [125][126][127][128][129][130]. Astringin, piceatannol glucoside, t-piceid, combretastatin A-4, t-isorhapontin, t-isorhapontigenin, and piceatannol represent the main stilbenes identified in the coniferous biomass, which exert various biological activities, including cardioprotective, neuroprotective, anti-inflammatory, antitumor, anti-diabetic [131], and antimicrobial effects [132] and also the inhibition of lipid peroxidation and scavenging of peroxyl radicals [133].…”
Section: Non-target Hrms Analysis For the Identification Of Additiona...mentioning
confidence: 99%